Ecoteology Of the Traditional Local Wisdom of Larung Sesaji at Lake Ngebel - Utomo, Tri Prasetiyo; Suyudi, M (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
Larung Sesaji at Telaga Ngebel, Ponorogo Regency is a unique local wisdom tradition. Telaga Ngebel is located at the foot of Mount Wilis. Telaga Ngebel is at an altitude of 737.23 meters above sea level. The surrounding community holds fast to the teachings of their ancestors. The ancestral teachings that are still preserved and exist are Purwa Ayu Mardi Utomo (PAMU). This belief system is a figure in the preservation of the Larung Sesaji tradition of Telaga Ngebel. The purpose of this research is to reveal the ecotheology of the local wisdom tradition of Larung Sesaji Telaga Ngebel which contains educational values, namely a non-formal educational process with an Eco theological approach that places the heterarchical order of the cosmos between humans, God, and nature. The research method uses a qualitative approach of the field study type. Data collection is carried out through observation, documentation, and interviews with community leaders (spiritual schools). Meanwhile, data analysis is carried out in four stages, namely data collection, data display, data reduction, and conclusion and verification. The results of the Larung Sesaji research contain Eco theological educational values of respect for nature, recognition of human limitations, and building harmony between living things and the environment (global tolerance). This local wisdom has proven to be a medium for ecological and spiritual education that grows from the cultural roots of the local community.